Problem-Based Learning (PBL) sebagai Strategi Pembelajaran Inovatif dalam Meningkatkan Hasil Belajar Kognitif Siswa pada Pembelajaran Biologi Kelas XI.A2 SMA Negeri 9 Pekanbaru - Marisha Silta Fany; Willyansah Willyansah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the application of Problem-Based Learning (PBL) as an innovative strategy to improve students' cognitive in biology class X.IA2 learning at SMA 09 Pekanbaru. The method used was qualitative through interviews with teachers and students and literature review was used to collect and analyze data. The results of the analysis show that PBL improves concept understanding, critical thinking, and problem solving. Teachers revealed that PBL creates more interactive learning, while students feel more motivated and active. The literature review also confirmed that PBL improves students' analytical power, creativity, and independence. The results recommend the widespread application of PBL to improve the quality of learning.